Reprints of Rare Papers on Mollusca: Bryant Walker (1918) A Synopisis of the Classification of the Fresh-Water Mollusca of North America, North of Mexico, and a Catalogue of the More Recently Described Species, With Notes - Bryant Walker (Hello World!, 1969)
The publications of the Museum of Zoology, University of Michigan, consist of two series- the Occasional Papers and the Miscellaneous Publications. Both series were founded and are being supported by Dr. Bryant Walker, Mr. Bradshaw H. Swales and Dr. W. W. Newcomb, except that the cost of the illustrations and of distribution are borne by the University.